Determinant Analysis of Low Birth Weight among Young Pregnant Women in Blitar District - Etti Suryani; Yuly Peristiowati; Yenny Puspitasari (Journal for Quality in Public Health, 2020)
Background : Low birth weight, commonly called LBW, is a major cause of infant mortality in Indonesia whereas its prevalence tends to increase from year to year. Purpose: This study aimed to analyze the determinants of gravida status, routine antenatal care, and comorbidities in LBW among young pregnant women in Blitar. Method : The research design was case-control using proportional cluster random sampling with a sample of 223 respondents. The data were analyzed with the binary logistic regression. Results : The results showed 214 respondents (96%) were primigravida, 23 respondents (10.3%) were not attended antenatal care routinely, 66 respondents (30%) had comorbidity, and 20 respondents (9%) delivered LBW baby. The statistical analysis of logistic regression showed there was no influence from gravida status and comorbidities, and routine antenatal care indicateda p-value of 0.000 which meant it was determined LBW among <20 years old pregnant women in Blitar. The interpretation of odd value was the group of < 20 years old pregnant women who were not attended routine ANC had a risk of 10 times to deliver LBW baby compared to the group of < 20 years old pregnant women who attended routine ANC. Conclusion : This study concluded that routine antennal care might prevent LBW for young pregnant women